1994
DOI: 10.1159/000183930
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Cushing’s Syndrome: Report of Three Cases and Literature Review

Abstract: Pre-Cushing’s syndrome (PCS) is defined as an overproduction of cortisol by an adrenal adenoma, without physical changes on clinical examination. Three patients with PCS were recently diagnosed among 21 consecutive patients suffering from adrenal ‘incidentaloma’. All patients showed nonsuppression of serum and urinary cortisol following 2 and 8 mg of dexamethasone (DXM), and suppressed or normal baseline plasma ACTH. Unilateral uptake of radiolabelled iodocholesterol, which persisted after DXM, was uniformly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Our first major finding is that, in agreement with several reports (Reincke et al, 1992;Fernandez-Real et al, 1994;Osella et al, 1994;Mantero et al, 1997;Barzon et al, 1998;Terzolo et al, 1998;Mantero et al, 2000;Sworczak et al, 2001), patients with adrenal incidentalomas frequently show isolated subtle subclinical endocrine alterations. Several terms have been adopted to define these forms, on the basis of the hormone involved, such as pre-, subclinical or silent Cushing's syndrome, and preclinical hyperaldosteronism or pheochromocytoma, but the clinical significance of these abnormalities remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Our first major finding is that, in agreement with several reports (Reincke et al, 1992;Fernandez-Real et al, 1994;Osella et al, 1994;Mantero et al, 1997;Barzon et al, 1998;Terzolo et al, 1998;Mantero et al, 2000;Sworczak et al, 2001), patients with adrenal incidentalomas frequently show isolated subtle subclinical endocrine alterations. Several terms have been adopted to define these forms, on the basis of the hormone involved, such as pre-, subclinical or silent Cushing's syndrome, and preclinical hyperaldosteronism or pheochromocytoma, but the clinical significance of these abnormalities remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported an occurrence of SCS that ranged 5-20% [6][7][8][9][10][11][12][13][14][15][16][17]. Hensen et al found cortisolproducing adenomas in 6% of all incidentally detected adrenal tumors [6], whereas McLeod et al reported a 5% prevalence cortisol-producing tumors in 122 patients with adrenal incidentaloma [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported increasing evidence that subtle cortisol production and abnormalities in the hypothalamic-pituitary-adrenal (HPA) axis are more frequent than previously thought. Depending on the diagnostic criteria and the study design used, SCS is found in 5% to 20% of patients with adrenal incidentaloma [6][7][8][9][10][11][12][13][14][15][16][17]. It is assumed that glucocorticoid production in these patients is insufficient to cause a clinically recognizible syndrome.…”
mentioning
confidence: 99%
“…Low dehydroepiandrosterone sulfate (DHEAS) levels are frequently observed in patients with adrenal incidentalomas even if the reason for this reduction remains to be fully clarified (7)(8)(9)(10). Conversely, high DHEAS levels are a marker of adrenal androgen excess that may herald the presence of an adrenal carcinoma (11).…”
Section: Introductionmentioning
confidence: 99%